Hydrophilic Modification of Polyester/Polyamide 6 Hollow Segmented Pie Microfiber Nonwovens by UV/TiO2/H2O2 - Baobao Zhao; Xu Han; Chenggong Hu; Xiaoming Qian; Yongchao Duo; Zhen Wang; Quan Feng; Quan Yang; Dongxu Han (Molecules, 2023)
Polyester/polyamide 6 hollow segmented pie bicomponent spunbond hydro-entangled microfiber nonwovens (PET/PA6) with a microfilament structure have recently emerged in many markets around the world due to their green, high-strength, and lightweight properties. However, PET/PA6 is highly hydrophobic, which inhibits its large-scale application at present. In order to enhance the hydrophilic performance of PET/PA6, many methods have been applied, but the effects are not obvious. Ultraviolet (UV) irradiation treatment has proven to be an effective method to improve the hydrophilicity of fabrics. Herein, the aim of this paper was to investigate hydrophilic modification of PET/PA6 by UV/TiO2/H2O2. The effect of H2O2, nano-TiO2, and UV irradiation time on the morphology, elemental composition, hydrophilic properties, and mechanical properties of PET/PA6 were systematically investigated. The results showed that the modified microfibers were coated with a layer of granular material on the surface. It was found that the C 1s peak could be deconvoluted into six components (C–C–C, C–C–O, O–C=O, N–C=O, N–C–C, and C–C=O), and a suitable mechanism was proposed. Moreover, the water contact angle of PET/PA6 modified by 90 min irradiation with UV/TiO2/H2O2 decreased to zero in 0.015 s, leading to the water vapor transmission rate and the water absorption reaching 5567.49 g/(m2·24 h) and 438.81%, respectively. In addition, the modified PET/PA6 had an excellent liquid wicking height of 141.87 mm and liquid wicking rate of 28.37 mm/min.